Anticoagulation, therapy of concomitant conditions, and early rhythm control therapy: a detailed analysis of treatment patterns in the EAST - AFNET 4 trial. Issue 4 (2nd September 2021) - Metzner, Andreas; Suling, Anna; Brandes, Axel; Breithardt, , Günter; Camm, A John; Crijns, Harry J G M; Eckardt, , Lars; Elvan, , Arif; Goette, , Andreas; Haegeli, , Laurent M; Heidbuchel, , Hein; Kautzner, , Josef; et al.
Abstract: Aims: Treatment patterns were compared between randomized groups in EAST-AFNET 4 to assess whether differences in anticoagulation, therapy of concomitant diseases, or intensity of care can explain the clinical benefit achieved with early rhythm control in EAST-AFNET 4. Methods and results: Cardiovascular treatment patterns and number of visits were compared between randomized groups in EAST-AFNET 4. Oral anticoagulation was used in >90% of patients during follow-up without differences between randomized groups. There were no differences in treatment of concomitant conditions between groups. The type of rhythm control varied by country and centre. Over time, antiarrhythmic drugs were given to 1171/1395 (84%) patients in early therapy, and to 202/1394 (14%) in usual care. Atrial fibrillation (AF) ablation was performed in 340/1395 (24%) patients randomized to early therapy, and in 168/1394 (12%) patients randomized to usual care. 97% of rhythm control therapies were within class I and class III recommendations of AF guidelines. Patients randomized to early therapy transmitted 297 166 telemetric electrocardiograms (ECGs) to a core lab. In total, 97 978 abnormal ECGs were sent to study sites. The resulting difference between study visits was low (0.06 visits/patient/year), with slightly more visits in early therapy (usual care 0.39 visits/patient/year; early rhythm control 0.45 visits/patient/year, P < 0.001), mainly due to visits for symptomatic AF recurrences or recurrent AF on telemetric ECGs. Conclusion: The clinical benefit of early, systematic rhythm control therapy was achieved using variable treatment patterns of antiarrhythmic drugs and AF ablation, applied within guideline recommendations.